2015
DOI: 10.1007/s11469-015-9567-9
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Expressed Emotion of Caregivers in Cases of Adult Substance Use Disorder with and Without Attention Deficit/Hyperactivity Disorder or Autism Spectrum Disorder

Abstract: ObjectiveTo identify and compare caregiver burden and expressed emotion (EE) in adult substance use disorder (SUD) patients with and without co-occurring attention deficit/hyperactivity disorder (ADHD) or autism spectrum disorder (ASD). To examine possible differences in correlations between caregiver burden and EE across patient groups.Design and MethodsCross-sectional study with measures of perceived burden (Involvement Evaluation Questionnaire: IEQ), subjective stress (General Health Questionnaire: GHQ) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
2
14
1
Order By: Relevance
“…This result suggests that the caregiver's worrying, coping, and subjective burden could depend mainly on behaviours and situations characteristic of BPD, such as suicide threats, self‐harm, abandonment of goal‐directed activity, emotional instability, or suicide attempts, rather than on the presence of other mental disorders such as eating disorders, substance abuse disorder, or major depression disorder. Our result is consistent with the Kronenberg et al () study, where caregivers of people with substance abuse with comorbidity had a similar caregiver burden to caregivers of people with substance abuse without psychiatric comorbidity. However, future research should replicate this study in larger samples that allow a multigroup CFA of measurement invariance for caregivers of people with BPD with and without psychiatric comorbidity.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result suggests that the caregiver's worrying, coping, and subjective burden could depend mainly on behaviours and situations characteristic of BPD, such as suicide threats, self‐harm, abandonment of goal‐directed activity, emotional instability, or suicide attempts, rather than on the presence of other mental disorders such as eating disorders, substance abuse disorder, or major depression disorder. Our result is consistent with the Kronenberg et al () study, where caregivers of people with substance abuse with comorbidity had a similar caregiver burden to caregivers of people with substance abuse without psychiatric comorbidity. However, future research should replicate this study in larger samples that allow a multigroup CFA of measurement invariance for caregivers of people with BPD with and without psychiatric comorbidity.…”
Section: Discussionsupporting
confidence: 93%
“…Only Bailey and Grenyer () found that a family context with high emotional overinvolvement in care was related to higher burden in caregivers of people with BPD. In the same way, in a study with caregivers of people with substance abuse, the EE from the perspective of the caregivers significantly correlated with the IEQ scores for caregiver burden (Kronenberg, Goossens, van Busschbach, van Achterberg, & van den Brink, ). Keeping in mind that previous studies on other mental disorders have identified an association between elevated emotional overinvolvement, higher distress, and reduced wellbeing in caregivers (Boye et al, ; Jeppesen et al, ; Vaughn et al, ), it is necessary to analyse whether EE is associated with caregivers' experience of burden and the consequences of providing care to people with BPD.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…In other words, medical conditions that require the greatest caregiving time may not exert the greatest levels of burden to caregivers. One way to explain this nding is that though some medical conditions may require a less alarming amount of caregiving time, the intensity and emotion strain of caregiving involved in taking care of the patients may be equally, if not more, burdensome [18,28,31,32,[62][63][64]. While this nding helps shed light on the relationship between caregiving time and caregiver burden, it also emphasizes the need for more research to further chart factors that in uence caregiving time and caregiver burden (e.g., disease severity [65]).…”
Section: Discussionmentioning
confidence: 99%